Electrochemical stability and electron transfer across 4-methyl-4′-(n-mercaptoalkyl) biphenyl monolayers on Au(100)-(1×1) electrodes in 1-hexyl-3-methylimidazolium hexafluorophosphate ionic liquid. (20th March 2017) - Martínez-Romero, N.E.; Aguilar-Sánchez, R.; Fu, Y.-C.; Homberger, M.; Simon, U.
Abstract: Electrochemical studies were carried out to explore the electrochemical stability and charge transfer properties of self-assembled monolayers (SAMs) of 4-methyl-4′-(n-mercaptoalkyl) biphenyl (CH3 -C6 H4 -C6 H4 -(CH2 )n -SH, n = 1–6, BP n ) on charged Au(100)-(1 × 1) electrodes, using the ionic liquid (IL) 1-hexyl-3-methylimidazolium hexafluorophosphate (HMImPF6 ) as reaction medium. We address relevant properties of the monolayers as the electrochemical stability, which is enhanced in the ionic liquid. The monolayers have low ionic permeability and their total electrochemical stability was approximately 3.0 V on Au(100)-(1 × 1) surface by using HMImPF6 as electrolyte. The hindered desorption of the BP n monolayer in ionic liquid seems to be due to a slow kinetic effect during the detachment of the monolayers. Odd-even effects were found for the charge transfer of the ferrocene redox reaction in presence of the BP n -adlayer.